Formulation and In Vitro Evaluation of Taste- Masked Prednisolone Orodispersible Tablets - Suzi, Hiba M.; B. H. Al-Khedairy, Eman (Journal of the Faculty of Medicine Baghdad, 2023)
Background: prednisolone is a corticosteroid with a very bitter taste acts as anti-inflammatory and immune suppressant drug and is used at any age.Objective: To improve patient compliance by masking the bitter taste of the drug to be delivered as orodispersible tablets.Methods: External ionic gelation using sodium alginate (0.5%w/v) and calcium chloride (1% w/v) in the presence of 0.5% w/v carbopol 940 was used to prepare taste-masked beads loaded with prednisolone to be compressed as orodispersible tablets.  Results:  The bitter taste was masked by preparing beads composed of 1:1:1 (sodium alginate: Carbopol 940: prednisolone) releasing only 0.77 % of the drug in pH 6.8 (pH of the oral cavity).The ODT prepared by direct compression using taste-masked beads equivalent to 5 mg PRD, 3% crospovidone, 2% PVP, 1% talc, 1% magnesium stearate, and a combination of Avcil® PH 102 and mannitol at (1:1) ratio was the optimum formula  (T6) with the hardness of 3.9± 0.32 kg, friability 0.45%, thickness 2.5 ± 0.05 mm, % drug content  98.2% ± 1.8, wetting time 18.7 ± 1.3 sec, water absorption 41 ± 2.1%, disintegration time 15.3 ± 0.5 sec. and released only 0.75% ± 0.01 of PRD in an oral pH of 6.8 within one minute (indicating good taste masking). Its release in the stomach (pH 0.1N HCl) and intestine (pH 6.8) was continued for up to two hours.   Conclusion: it can be concluded that the external ionic gelation method was successful in masking the bitter taste of prednisolone and also can be formulated as taste-masked orodispersible tablets by direct compression method.